“Shall we apply for a flat?” Examining the decision-making processes of young homeowners in Singapore - See, Dionne Yan Ting (2016)
There are many living alternatives available in Singapore. There is high homeownership but most live in public Housing Development Board (HDB) flats. The demand for Build-To-Order (BTO) flats is increasing despite the long wait and poorly serviced flats in the initial years of development. Past studies have emphasized the aspiring mobility of middle class Singaporean thus this study seeks to study why one would still opt for BTO flat. Findings have shown that decision-making processes are usually unconscious due to interventions of the state in the private affairs of the people. Young homeowners are realistic when they make huge decisions about thus they utilize other consumer items instead of housing type to socially distinguish them. Young homeowners do long-term planning thus is willing to compromise initially for their first house. However, state intervention is limited due to strong individuality character of young Singaporeans.